Modern approaches to forming pedagogue’s communicative competency - Штефан, Л. В. (Scientific notes of the pedagogical department, 2019)
Modern educator exists in a socially and psychologically complex environment, which requires it a significant health resource. In view of this, an approach based on the concept of salutogenesis, which in translation means «health creation», is a matter of interest. The health of the teacher is the result of his harmonization in the educational space. Exiting the harmonious state largely depends on the success of pedagogical communications. Therefore, the issue of formation of communicative competence in the context of preserving the health of the teacher becomes relevant. This can be achieved today thanks to the updating of the communicative toolkit. As the last one, the techniques of neurolinguistic programming (NLP) are offered. If the basic principles of the activity will be the principle of humanism, skillful possession of NLP techniques, the subject-subject interaction of the participants in the educational process will be more productive, less energy-consuming and minimally conflictual. And all this in a complex will save the main welcome resource of the teacher – health. Analytical work allowed to conclude that the main provisions of salutogenesis, the structural components of the communicative competence of the teacher and the basic approaches of NLP are coherent. On this basis in the article a model of communicative competence of the teacher is developed on the basis of coherence with the field of resources of NLP and the field of salutogenesis. It is shown that the field of NLP resources creates the necessary base of techniques for forming the field of communicative competence of the teacher. In this case, the field of NLP resources is external coherent with the field of communicative competence, which in the future allows for efficient communication. On this basis, the basic provisions of the field of salutogenesis are logically implemented. This is possible due to the fact that the field of communicative competence is externally coherent with it. Thus, the harmonization of communication in pedagogical activity takes place and the basis for the health of the teacher is formed.